The Association of Antibody Levels with Body Mass Index, Stress Management Ability and Lipid Peroxidation in Patients with Hashimoto’s Thyroiditis - Murat Giriş; İlknur Bingül; Alper Şahbaz; Hande Parıldar Karpuzoğlu; Sami Açar; Yunus Yapalak; Yeşim Erbil (The Turkish Journal of Ear Nose and Throat)
Objective: The potential predictive value of body mass index, stress management ability, and thiobarbituric acid reactive substances (TBARS) levels for antibody levels in Hashimoto’s thyroiditis (HT) were evaluated.Materials and Methods: Two hundred patients with HT were included in the study. The patients were allocated into four groups as Group 1, patients with a body mass index (BMI) of 30 or higher (n=54); Group 2, patients with stress management difficulties (n=59); Group 3, patients with a BMI higher than 30 and stress management difficulties (n=11), and Group 4 (control, n=76), those without obesity or stress management issues. The mean age of patients, BMI, stress management abilities, anti-thyroid peroxidase (anti-TPO) antibodies levels, weekly T4 drug dosages, duration of levothyroxine usage, quality of life scores, as well as thiobarbituric acid reactive substances (TBARS) were evaluated.Results: The antibody levels were significantly associated with body mass index and stress management. The antibody level increased 533 times (p<0.0001) in the group without stress management difficulties, and was affected 525 times (p<0.0001) in the obesity group.Conclusion: The findings of our investigation revealed that stress management ability and obesity are the important factors influencing antibody levels.